Governance Policy on The Impact of Marble Mining Activities in Tulungagung Regency Reviewed from the Perspective of Sustainable Development - Muhammad Rama Sanjaya; Kasyful Azhim (West Science Law and Human Rights, 2024)
This research aims to analyze governance policies on the impact of marble mining activities in Tulungagung Regency from a sustainable development perspective. Marble mining activities in this area have significant environmental, social and economic impacts. This research uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with stakeholders, field observations, and analysis of related policy documents. The research results show that although there have been efforts to integrate sustainable development principles in marble mining governance policies, implementation still faces various challenges. Some of these include a lack of supervision and law enforcement, as well as limitations in community participation. This study recommends increasing the capacity of management institutions, strengthening community participation, and increasing coordination between sectors as strategic steps to increase the sustainability of marble mining activities in Tulungagung Regency.